The Role of The School Environment as A Moderating Variable in The Effect of Discipline on Learning Outcomes in Islamic Religious Education and Ethics - Indriyanti, Dwi Cahyani; Cahyono, Guntur (Kalijaga Journal of Islamic Religious Education, 2025)
his study aims to analyze the influence of discipline on Islamic Religious Education and Ethics learning outcomes and to examine the role of the school environment as a moderating variable. The research approach employed quantitative methods with a survey technique. The study population consisted of 218 seventh-grade students of SMP Negeri 2 Salatiga in the 2024/2025 academic year, and 69 students were selected as a sample using the Slovin formula with a 5% margin of error. Data were collected through questionnaires (for discipline and school environment variables) and grade documentation (for learning outcomes). Data analysis was performed using multiple linear regression and Moderated Regression Analysis (MRA) using SPSS. The results indicate that discipline has a positive and significant influence on Islamic Religious Education and Ethics learning outcomes. Furthermore, the school environment acts as a moderating variable, strengthening the influence of discipline on learning outcomes when conditions are conducive and weakening it when conditions are less conducive. These findings confirm that improving the quality of Islamic Religious Education and Ethics learning is not solely determined by internal factors such as student discipline, but also influenced by external factors such as a supportive school environment. Practically, these research findings provide implications for educators and school administrators to foster a culture of discipline and create a religious, orderly, and conducive learning climate as an effort to improve the quality of religious education.